2015
DOI: 10.1530/endoabs.38.ja2
|View full text |Cite
|
Sign up to set email alerts
|

1,25-vitamin D3 promotes cardiac differentiation through modulation of the WNT signaling pathway

Abstract: Cardiovascular disease (CV) remains the leading cause of death worldwide. Low levels of vitamin D are associated with high risk of myocardial infarction, even after controlling for factors associated with coronary artery disease. A growing body of evidence suggests that vitamin D plays an important role in CV related signaling pathways. However, little is known about the molecular mechanism by which vitamin D modulates cardiac development. The Wnt signaling pathway plays a pivotal role in tissue development by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Consistent with the hypothesis, there was enrichment for "Differentiation of Epithelial Tissue" at both time points with sufficient 1,25D (Supplemental Figure S6, red box). The Wnt pathway was selected for additional investigation in the primary prostate cells because previous studies in the RWPE1 prostate cell line, gut, skin and heart have shown 1,25D inhibition of canonical Wnt signaling (Aguilera et al, 2007;Hlaing et al, 2014;Kovalenko et al, 2010;Larriba et al, 2011;Muralidhar et al, 2019).…”
Section: 25d Modulates the Wnt Pathway In Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the hypothesis, there was enrichment for "Differentiation of Epithelial Tissue" at both time points with sufficient 1,25D (Supplemental Figure S6, red box). The Wnt pathway was selected for additional investigation in the primary prostate cells because previous studies in the RWPE1 prostate cell line, gut, skin and heart have shown 1,25D inhibition of canonical Wnt signaling (Aguilera et al, 2007;Hlaing et al, 2014;Kovalenko et al, 2010;Larriba et al, 2011;Muralidhar et al, 2019).…”
Section: 25d Modulates the Wnt Pathway In Organoidsmentioning
confidence: 99%
“…Genes regulated by vitamin D are involved in proliferation, differentiation, and apoptosis pathways (Feldman et al, 2014). Vitamin D metabolites are pro-differentiating in a variety of cell and tissue types, including keratinocytes (MacLaughlin et al, 1990), intestinal villi (Peregrina et al, 2015;Spielvogel et al, 1972), cardiomyocytes (Hlaing et al, 2014), odontoblasts (Mucuk et al, 2017), placenta (Hutabarat et al, 2018), and macrophages (Abe et al, 1981;James et al, 1997). While some of these studies explore 1,25D action in benign cells, the majority of reports focus on vitamin D inhibition of cancer cell growth and tumor progression (Aguilera et al, 2007;Banks and Holick, 2015;Holick et al, 2007;Larriba et al, 2011;Tavera-Mendoza et al, 2017;Yang et al, 2017), and very little is known about the pro-differentiating activity of vitamin D in benign prostate.…”
Section: Introductionmentioning
confidence: 99%